Quality of life and osteomuscular symptoms in workers of primary health care - João Roberto Cordioli Junior; Dezolina Franciele Cardin Cordioli; Claudia Eli Gazetta; Albertina Gomes da Silva; Luciano Garcia Lourenção (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to evaluate the quality of life and musculoskeletal symptoms in primary care workers. Methods: descriptive, correlational and cross-sectional study with 85 workers using the WHOQOL-Bref and Nordic Osteomuscular Symptoms Questionnaire. Results: lower quality of life for the Environment domain and higher for Social Relationships. Workers reported pain in lower back, neck, shoulders, wrists/hands/fingers and knees. Neck pain influenced Physical (p=0.015) and Psychological (p=0.030) domains; shoulder pain (p=0.004) and dorsal region (p=0.013) influenced the Physical domain; pain in knees influenced Physical (p=0.000) and Environment (p=0.032) domains; pain in the ankles/feet influenced Physical (p=0.000), Psychological (p=0.032) and Environment (p=0.007) domains; pain in the dorsal region influenced the Physical domain (p=0.013). Conclusions: workers evaluated their quality of life as good or very good and reported to be satisfied or very satisfied with their health. They also reported pains in lower back, neck, shoulders, wrists/hands/fingers and knees. Pain has influenced the quality of life.